The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1007/s10639-021-10831-6
|View full text |Cite
|
Sign up to set email alerts
|

Learning design to support student-AI collaboration: perspectives of leading teachers for AI in education

Abstract: Preparing students to collaborate with AI remains a challenging goal. As AI technologies are new to K-12 schools, there is a lack of studies that inform how to design learning when AI is introduced as a collaborative learning agent to classrooms. The present study, therefore, aimed to explore teachers’ perspectives on what (1) curriculum design, (2) student-AI interaction, and (3) learning environments are required to design student-AI collaboration (SAC) in learning and (4) how SAC would evolve. Through in-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 56 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…According to a few researches on the topic, academic integrity can be improved through the use of plagiarism checkers, proctoring, or monitoring of students' activities via online platforms like Grammarly, TurnItIn or White Smoke (J. Kim et al, 2022). It's been shown in other studies that teamviewer applications, simulation, and gamification have significant benefits to instructional quality, alongside being closely linked to VR and 3-D or even using the techniques to increase performance and effectiveness through the use of AI.…”
Section: Instructionmentioning
confidence: 99%
“…According to a few researches on the topic, academic integrity can be improved through the use of plagiarism checkers, proctoring, or monitoring of students' activities via online platforms like Grammarly, TurnItIn or White Smoke (J. Kim et al, 2022). It's been shown in other studies that teamviewer applications, simulation, and gamification have significant benefits to instructional quality, alongside being closely linked to VR and 3-D or even using the techniques to increase performance and effectiveness through the use of AI.…”
Section: Instructionmentioning
confidence: 99%
“…To fully utilize these tools, students may need writing strategies, which appear to help youths to focus, to address difficulties in the writing process and to improve the quality of their writing (Crossley et al, 2016). In other words, by integrating the generated contents into their written compositions, students are learning from AI, that is, actively and independently developing strategies to work and to interact with AI to complete a task (Kim et al, 2022).…”
Section: Perspective(s) or Theoretical Frameworkmentioning
confidence: 99%
“…AI technologies are new to K-12 schools (Kim et al, 2022) and AI is a new subject area for K-12 schools around the world (UNESCO, 2022). In spite of little historical knowledge about how to conceptualize AI integration in education programs, progress has been made in some directions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Cheng (2021) have suggested three different directions for AI in curriculum, learning from AI, learning about AI and learning with AI. Similarly, Kim et al (2022) suggested AI in curriculum might develop in three stages: learning about AI; learning from AI; and learning together. As for essential outcomes, Ng et al (2022) have proposed four cognitive standards: know and understand AI; use and apply AI; evaluate and create AI; and AI ethics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation